Implantación De Un Sistema De Contabilidad A La Lubricadora “Lubryllant” Del Cantón Catamayo, Provincia De Loja, Período: Abril-Junio Del 2016 - Neira Espinosa., Mónica María (2017)
The present thesis entitled "IMPLEMENTATION OF AN ACCOUNTING SYSTEM TO LUBRICADORA" LUBRYLLANT "OF CANTÓN CATAMAYO, STATE PROVINCE, PERIOD: APRIL-JUNE 2016", was carried out with the purpose of applying an accounting system to the commercial one according to its Activities, in order to determine in a real and timely manner the economic and financial situation in which it is located, providing a significant contribution to the owner, with which it will be able to make sound decisions in the management of the same. In compliance with the objectives set, the source documentation for the months of April-June 2016 was compiled, which collected the necessary information to control and record the economic activities of the Lubricator. Following the objectives, sales and purchasing assistants were designed to provide an orderly and analytical detail of the daily transactions that are presented, the accounts receivable assistant that controls credit sales to customers and the account assistant by Pay that allows to disaggregate the movement of credits and charges to the suppliers. Subsequently, the accounting process was developed, through the multiple account system, from the initial inventory through the physical verification of the assets, values and obligations that the company possesses, Initial Status, journal, general ledger, checking balance , Worksheet, adjustments, financial statements and finally the financial indicators were applied with their respective interpretations to measure the degree of liquidity, activity, profitability and indebtedness in which the commercial is.At the end of the accounting process the conclusions are presented, where it was found that the company did not have an accounting system or the application of financial indicators, which did not allow it to know the economic and financial situation of the company, so it is recommended To the owner to continue applying this system, in order to know their current economic situation and to make timely decisions to improve the administration and efficiency of the business.